Polylactide foams : fundamentals, manufacturing, and applications - Nofar, Mohammadreza, 1983-; Park, Chul B. (PDL handbook series., 2018)
Polylactide Foams: Fundamentals, Manufacturing, and Applications provides an introduction to the fundamental science behind plastic foams, polylactic acid) and polylactide foaming, giving designers tactics to replace traditional resins with sustainable and biodegradable materials. The book then delves deeper into the technology behind PLA foaming, such as PLA/gas mixture characteristics, solubility, interfacial tension behaviors and crystallization kinetics of various types of PLA and their compounds. The foaming behaviors and mechanisms of various types of PLA and PLA compounds are extensively analyzed and discussed through different manufacturing technologies, namely extrusion foaming, foam injection molding and bead foaming. Interest in Poly(lactic acid) and PLA foams is extremely high - particularly as a potential replacement for styrenic resins - and the price of PLA resin is lower than ever before. This biopolymer has significant potential to improve the sustainability of the plastics industry. Polylactide Foams have a range of potential applications, such as in construction, packaging, insulation, biomedical scaffolds, and others. However, processing and performance of PLA are not at the same level as other non-biodegradable resins.